Hearing Improvement after Type-1 Tympanoplasty in Chronic Otitis Media - Safi, Md Abdullahis; Karim, Md Anayet; Islam, Md Aminul (Bangladesh Armed Forces Medical Journal, 2025)
Background: Chronic otitis media means chronic inflammation of mucosa of middle ear cleft which is defined by continuous or intermittent ear discharge through a tympanic membrane perforation. COM is now appearing as a significant problem causing hearing loss in our country. The occurrence of COM is overwhelmingly high in the developing countries like Bangladesh due to poor living condition, high rate of population, less knowledge of personal hygiene, malnourishment, tobacco intake, inadequate health education etc. COM can be treated with Tympanoplasty. Objective: To assess the hearing improvement after type-1 tympanoplasty. Method: The study was conducted over 35 patients by prospective observational method who were attending the ENT OPD from March 2022 to Februry 2024 irrespective of age and sex who went through tympanoplasty (Type-1). Preoperative and postoperative audiometry was done in all patients to assess the hearing improvement. Post-operative hearing assessment was done at 3 and 6 month after surgery. Results: In this study, majority were in between 21 to 30 years. The female and male ratio in this study is 1.3:1. Among all patients 8 (22.86%) presented with anterior perforations, 16 (45.71%) presented with central perforations and 11 (31.43%) presented with posterior perforations. While majority of cases 16 (45.71%) were presented with small perforations, 9 (25.71%) presented with medium perforations and 10 (28.57%) presented with large perforations. After type-1 tympanoplasty 25 (71.43%) patients gained their normal hearing ability, 9 (25.71%) improved up to mild degree range and only 1 (2.86%) patient showed no significant improvement. In case of small perforations, the mean AB gap was 33.32 dB, in medium perforation AB gap was 38.04 dB and in large perforation AB gap was 49.44 dB before surgery. The AB gap after surgery in case of tiny perforations was 9.89 dB, in case of moderate perforations AB gab was 18.34 dB Indicate significant hearing improvement and in case of large perforations the mean AB gap was 48.89 dB that indicates less hearing improvement. Conclusion: There was significant hearing improvement after type-1 tympanoplasty in case of small perforation (P value <.001) but in case of large perforation there was no satisfactory improvement (P value = 0.701) in hearing status. Thus, size of perforation have significant impact in hearing improvement after type-1 tympanoplasty according to this study. Bangladesh Armed Forces Med J Vol 57 No (2) December 2024, pp 7-13